FORECASTING WHEAT AREA AND PRODUCTION IN NEPAL USING AUTOREGRESSIVE INTEGRATED MOVING AVERAGE MODEL (ARIMA) - BIBEK GAUTAM; SUSHMA ADHIKARI (Innovare Journal of Agricultural Sciences, 2024)
Wheat is one of the major staple crops of Nepal grown from Plains to high hills. Nepal has observed the increased production of wheat in the last decade but is unable to produce enough to meet country demand. Autoregressive Integrated Moving Average Model (ARIMA) was implied to forecast the Wheat area and production in Nepal from 2021 to 2030 using available data from FAO. Rstudio software with forecast package using “auto.arima ()” was used for selecting the suitable model. On analysis, it was observed that ARIMA model (2,1,3) and (0,1,0) were found appropriate for the forecasting of production and area of wheat with lowest Akaike’s information criterion 682.01 and 537.76 respectively among competitive models. Results from the model suggested the increase in the area and production of the wheat by 1.32% and 1.72%, respectively, but on decreasing rate which suggests to act in the productivity increasing traits for achieving food security.